PERILAKU MENYIMPANG PADA REMAJA DAN AKHLAK DALAM PERSPEKTIF ISLAM - Sofia Azzahra; Miftahul Jannah; Mahmud , Salami (Fakultas Tarbiyah IAI Almuslim Aceh, 2025)
Humans are born as powerless individuals without knowledge. Over time, deviant behavior among adolescents has become an increasingly widespread social issue. Adolescents are highly dependent on the role of parents in shaping their morals and behavior. This study employs a library research method aimed at analyzing various literatures concerning moral deviation among adolescents. The findings identify several forms of deviant behavior, including: (1) alcohol consumption, (2) drug abuse, (3) student brawls, (4) premarital sexual behavior, (5) gambling, and (6) criminal acts. Moral problems among adolescents do not arise spontaneously but are the result of complex interactions between internal and external factors. The main contributing factors include: (1) family dysfunction, (2) lack of religious education, (3) peer and environmental influence, and (4) the negative impact of social media and technology.